Orthopedic Case Burden at Nunukan Hospital: Focus On Trauma Case - Pandji Winata Nurikhwan; Ahmad Muhsinin; Zairin Noor (Berkala Kedokteran, 2019)
Abstract: Incidence of orthopedic case is quite high in Nunukan Hospital, most of them need both non-operative and surgical intervention due to congenital, debridement, fracture, rupture of tendon and blood vessel, even amputation. Until now, data orthopedic case profile especially trauma case in Nunukan Hospital is not available. Also, the urgency of having an orthopedic surgeon is unbearable which unavailable in Nunukan, this made the management can’t be done comprehensively and as soon as possible. The aim of this research was to describe the incidence of orthopedic case at Nunukan hospital as basic data for further research. This Retrospective Study was conducted at Nunukan Hospital, North Kalimantan – Indonesia. The data is collected by using logbook and medical records during January 2016 - April 2017. Total of 231 cases were obtained. Male patients accounted for 73.6% (170 patients) and Female was 26.4% (61). The age ranged from 1 day to 82 years old. There are 8-21 cases happened per month (average: 14 cases). Based on case category, trauma occurred for 88.7%% (205). Five top diagnoses are; Close Fracture happened for 44.6% (103 cases), followed by Open Fracture 17.7% (41 cases), Lacerated wound 11.3% (26 cases), Traumatic Amputation 7.4% (17 cases) and CTEV 7.4% (17 cases). Most pathology within the period located in Foot for 29.9% (69). The multiple fracture, vascular, and soft tissue injury were observed. Orthopedic fractures were the most common injuries among patients with 88.7% in Nunukan Hospital from January 2016 to April 2017. There are 14 cases happened for each month with most of the patient were adult. Most of injuries happened at foot region.Abstract: Incidence of orthopedic case is quite high in Nunukan Hospital, most of them need both non-operative and surgical intervention due to congenital, debridement, fracture, rupture of tendon and blood vessel, even amputation. Until now, data orthopedic case profile especially trauma case in Nunukan Hospital is not available. Also, the urgency of having an orthopedic surgeon is unbearable which unavailable in Nunukan, this made the management can’t be done comprehensively and as soon as possible. The aim of this research was to describe the incidence of orthopedic case at Nunukan hospital as basic data for further research. This Retrospective Study was conducted at Nunukan Hospital, North Kalimantan – Indonesia. The data is collected by using logbook and medical records during January 2016 - April 2017. Total of 231 cases were obtained. Male patients accounted for 73.6% (170 patients) and Female was 26.4% (61). The age ranged from 1 day to 82 years old. There are 8-21 cases happened per month (average: 14 cases). Based on case category, trauma occurred for 88.7%% (205). Five top diagnoses are; Close Fracture happened for 44.6% (103 cases), followed by Open Fracture 17.7% (41 cases), Lacerated wound 11.3% (26 cases), Traumatic Amputation 7.4% (17 cases) and CTEV 7.4% (17 cases). Most pathology within the period located in Foot for 29.9% (69). The multiple fracture, vascular, and soft tissue injury were observed. Orthopedic fractures were the most common injuries among patients with 88.7% in Nunukan Hospital from January 2016 to April 2017. There are 14 cases happened for each month with most of the patient were adult. Most of injuries happened at foot region.